Resilience in live peer-to-peer streaming. - Fodor, Viktoria; Dan, Gyorgy
The success of peer-to-peer overlays for live multicast streaming depends on their ability to maintain low delays and a low ratio of information loss end-to-end. However, data distribution over an overlay consisting of unreliable peers is inherently subject to disturbances. Resilience is thus inevitably a key requirement for peer-to-peer live-streaming architectures. In this article, we present a survey of the media distribution methods, overlay structures, and error-control solutions proposed for peer-to-peer live streaming. We discuss the trade off between resilience and overhead and argue that efficient architectures can be defined only through thorough performance analysis.
Keywords: Data distribution; Error-control solutions; Information loss; Live multicast streaming; Media distribution methods; Overlay structures; Peer-to-peer live streaming; Peer-to-peer overlays; Unreliable peers